Use of an Intrathecal Catheter for Analgesia, Anesthesia, and Therapy in an Obstetric Patient with Pseudotumor Cerebri Syndrome. Issue 6 (15th March 2016) - Gragasin, Ferrante S.; Chiarella, Angelo B.
Abstract : Pseudotumor cerebri syndrome (PTCS) is a rare disorder chiefly observed in obese women of childbearing age. We describe a case of a parturient with PTCS managed successfully with an intrathecal catheter, after inadvertent dural puncture, for labor analgesia, surgical anesthesia, and treatment of headache because of intracranial hypertension during the peripartum period. Prolonged placement of the intrathecal catheter (i.e., >24 hours) may have contributed to the absence of postdural puncture headache symptoms and an uneventful postpartum period. Intrathecal catheter placement may therefore be a viable option in patients with PTCS should inadvertent dural puncture occur.